(untitled) (Studia theodisca, 2014)
After depicting the core function of correspondence for understanding Hölderlin, as well as contextualizing the letter to his brother Carl (January 1st 1799) in both his life and work, a close reading of this document focuses step by step on its political, philosophical and first and foremost poetological issues.